Business cycles, entrepreneurship and economic growth dynamics : exploring the linkages; situating the policy options - Isu Hamilton Obiahu (Nigeria, Abuja : Book society of Nigeria, 2023)
Business cycles, entrepreneurship, and economic growth are intertwined, with entrepreneurship playing a crucial role in driving economic expansion and influencing the dynamics of business cycles. Understanding these linkages is vital for policymakers to formulate effective strategies that foster both sustainable growth and resilience to economic fluctuations.
Includes bibliographical reference and index
nmn, 07/08/25
Loans
Keywords: Business cycles; Entrepreneurship; Economic growth; Economic policy